Sustainability Analysis of Wae Batu Elephant River Flow Management Ambon City - Jusmy D. Putuhena (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The role of the Wae Batu Gajah watershed which has a function to regulate water management and as a water source is currently starting to experience a very significant change with the rate of change of forest land cover into settlements which ultimately destroys the sustainability of the ecological function. This damage can be proven by the phenomenon of flooding and that occurs in the rainy season and drought in the dry season. The analysis of the sustainability of the Wae Batu Gajah watershed has the following objectives: 1). Analyzing the index and sustainability status of the Wae Batu Gajah watershed from the ecological, economic and social dimensions. 2). Testing the validity and testing the accuracy of the sustainability index of the Wae Batu Gajah watershed management. The results of the study show that the multidimensional sustainability index for the three ecological, economic and social dimensions is 50.97% in the moderately sustainable category. The validation test shows the difference in the value of the Monte Carlo and MDS analysis at the 95% confidence level the average for the three dimensions is 0.72%; the value of determination (R2) between 93.86% - 95.18% means that the sustainability index estimation model is good and adequate; stress value 0.2, which means that the MDS analysis model obtained has a high accuracy (goodness of fit) to assess the sustainability index of the Wae Batu Gajah watershed.